1996
DOI: 10.1021/ic960131u
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Addition of CH, NH, and OH Bonds to the Phosphadiazonium Cation and Interpretation of 31P Chemical Shifts at Dicoordinate Phosphorus Centers

Abstract: The phosphadiazonium cation [MesNP](+) reacts quantitatively with the fluorenylide anion, MesNH(2), and MesOH (Mes = 2,4,6-tri-tert-butylphenyl), resulting in formal insertion of the N-P moiety into the H-Y (Y = C, N, O) bonds. Specifically, reaction of MesNPCl with fluorenyllithium gives the aminofluorenylidenephosphine [crystal data: C(31)H(38)NP, monoclinic, P2(1)/c, a = 9.568(8) Å, b = 24.25(2) Å, c = 11.77(1) Å, beta = 101.38(8) degrees, Z = 4]. Similarly, reaction of [MesNP][GaCl(4)] with MesNH(2) gives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
6

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 45 publications
1
58
0
6
Order By: Relevance
“…The only known aryl-substituted bis(amino)phosphenium cation 3 (E = Al, Scheme 2) was introduced by Niecke [9] and coworkers and further studied by Burford et al [10] As shown in Scheme 2, the phosphadiazonium cation [Mes*NP] + (2) reacts quantitatively with Mes*NH 2 (Mes* = 2,4,6-tri-tert-butylphenyl) to yield ECl 4 -salts with the bis(amino)phosphenium cation (Mes*3). The solid-state structures of Mes*3 [GaCl 4 ] and Mes*3 [AlCl 4 ] have been confirmed by X-ray crystallography and the structural parameters of the cation are essentially identical.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only known aryl-substituted bis(amino)phosphenium cation 3 (E = Al, Scheme 2) was introduced by Niecke [9] and coworkers and further studied by Burford et al [10] As shown in Scheme 2, the phosphadiazonium cation [Mes*NP] + (2) reacts quantitatively with Mes*NH 2 (Mes* = 2,4,6-tri-tert-butylphenyl) to yield ECl 4 -salts with the bis(amino)phosphenium cation (Mes*3). The solid-state structures of Mes*3 [GaCl 4 ] and Mes*3 [AlCl 4 ] have been confirmed by X-ray crystallography and the structural parameters of the cation are essentially identical.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of Mes*3 [ECl 4 ] (E = Al, Ga). [9,10] ride abstraction with Lewis acids in 2-chloro-1,3,2-diazaphospholenes (Scheme 3). [12] Chloride abstraction was also successfully applied in the isolation of salts that bear cyclo-1,3-diphospha-2,4-diazenium ions, which can also be regarded as carbene analogs (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the C-N-P bond angle is approximately linear, 169S0, it is reasonable to assume that the electric field gradient at the nitrogen centre will be nearly axially symmetric, with the largest component along the formal PN triple bond. From the known internuclear separation, rpTN = 1.486 (4) A (12), the dipolar coupling constant, R(1,S) = (p,d4.rr)(y,ysl r,,s3)(~/2.rr), can be calculated, 1070 Hz. With these values, analysis of the asymmetric doublets yields an upper limit for I ' J (~~P , '~N ) I of 25 Hz and a nitrogen nuclear quadrupolar coupling constant, X('~N), of -1.7(2) MHz.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this communication is to demonstrate the power of solid-state ,'P NMR experiments in determining the absolute sign and magnitude of ' J (~' P , ~~P ) for an adduct composed of a phosphadiazonium cation, [Mes*NP]+ (Mes* = 2,4,6-tri-tert-butylphenyl), and triphenyl hosphine, bound by an unusually long P-P bond of 2.625 lf (12). The results of this study clearly demonstrate that there is no simple, general relationship between 'J(~'P,~'P) and P-P bond order.…”
Section: Introductionmentioning
confidence: 99%